Computer semiotics as a possible framework for understanding computer-mediated communication - Kleut, Jelena (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
The paper presents computer semiotics, the area that follows the established path of semiotic interest in media specific systems of signification and communication. Computer semiotics is formed through multidisciplinary cross-fertilization of social and technical sciences. It presents a diverse field of research that can be viewed as a whole only if criteria is the usage of semiotic terms in explaining and analysing messages made with participation of computers. The semiotic conceptualisation of hypertextuality and multimodality is mostly known and accepted, and for that reason the paper presents the branch of computer semiotics in which the central place is given to structural parts of the new medium: software and interface. Software is viewed as the structural element of the medium in which the reality outside of computers is translated in reduced signs that can be processed. Interface is the structural part of the medium which presents software possibilities and digital objects. Interface intended for users is made in combination of technical codes at the level of software and cultural codes, without which users would not be able to interpret computer signs. The existence of software and user interface opens a set of questions to which computer semiotics aims to provide answers: what kind of signs are made, who participates in sign production, how are these participants represented, and how are cultural and technological factors intertwined in the new medium.
Keywords: semiotics; computer-mediated communication; INTERFACE; software; designer